Comparative evaluation of drug information leaflets for non-steroidal anti-inflammatory drugs in Palestine: local versus imported products - Dina A. Arandy; Maysa W. Abu-Hashia; Bahaa M. Al-hroub; Sandra A. Qatmosh; Amer A. Koni; Baraa G. Qeeno; Samah W. Al-Jabi; Sa'ed H. Zyoud (BMC, 2019)
Abstract Background Drug information leaflets (DILs) are written for patients and health care providers to show how to use the medications safely and effectively, in order to reach the required therapeutics outcomes. This comparative study was conducted to evaluate various DILs of non-steroidal anti-inflammatory drugs (NSAIDs) that are produced in Palestine, along with their imported equivalents. Methods Thirty-five DILs of NSAIDs were analyzed and evaluated in a cross-sectional comparative study. Thirty-one statements were obtained from literature and used; evaluation was performed on basis of both any presence or absence of these statements in the leaflets. 23 of the 31 statements that were available in both local and imported DILs were also evaluated in terms of total word-counts: the median (interquartile range) word-count for each statement was determined separately for the two groups and then compared. For the remaining 8 statements, this was not performed,either because they were not present in any leaflet, or because counting the number of words would not be meaningful. Results A total of 35 DILs for nine different active ingredients of NSAIDs were analyzed. In 97% of leaflets, "Instructions to convert medication into liquid forms" were missing and 94% did not provide any information about "Pharmacokinetics". 83% of DILs provided no information about "Mechanism of action" and 74% did not mention any reliable references. 66% of the analyzed inserts did not include any instruction about the possibility of a tablet splitting. And in 63%, the "Date of last revision" was missing. Further, "Duration of using" and "Inactive ingredients" were not found in 51% of leaflets. In terms of word-count, the related sections of the 23 selected criteria were expressed with more words by imported leaflets compared with the local ones, significant differences were found in 12 categories, the highest significance of > 42.4-fold difference was found in "Geriatric considerations" category whereas 1.4-fold difference was found in "Shelf life," being the lowest one. Conclusions This study shows that local products provide less information than imported products, so we recommend that appropriate measurements be taken by both Palestinian authorities and manufacturers to improve both quantity and quality of local DILs.